Postcard from Margaret Ripley to her sister, sent 8 December 1914... - whatsthatpicture from... (Wikimedia Commons, 2011)
Notice image issue de Wikimedia Commons. Titre: Postcard from Margaret Ripley to her sister, sent 8 December 1914 (6241452257). Sent by a nurse, Margaret Ripley, to her mother back in England. As far as I can tell (corrections and additions welcome) this reads: " 10.12.14 Paris Went into Notre Dame yesterday and pottered about. Louvre closed. St Chapelle closed so can only see churches & outsides, shops all shut between 6 & 7 & everyone goes to bed - cafes & all close before 8. weather fine but cold wind. Saw these flags [see image link below] the last only taken 10 days ago reast are in Bordeaux. Off to Dunkerque tomorrow (Monday) write there [P.R.?] all very pleased & hope it will be real work at last. Expect it {???] be typhoids. Seems ages since I had letter. We shall meet many friends there. Had been told to go to Rouen then Evreuse or Tours but we are pleased to have more real war work - if only we could {??????]. Love Mar " So we see Margaret in Paris as originally thought, and not going to Bordeaux after all. Her desire to work and help the war effort is clearly very strong. Has anyone else noticed though, the postmark on this card clearly reads "10-1 15" - so, who is wrong? For more details of the story behind this album see www.flickr.com/photos/whatsthatpicture/sets/7215762769463..., url = https://demo.fonds-documentaire.fr/detail.php?inventaire=1175, note = Licence CC BY 2.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; église; transport